Vibration control of commercial vehicle drive axles based on modification of helical gears. (15th June 2023) - Yang, Ji-xuan; Chen, Zhi-yong; Shi, Wen-ku; Yuan, Ren-fei; Liu, Jian; Zhao, Yan-yan
Highlights: A coupled kinetic-finite element model of drive axle assembly is developed. Sensitivity analysis of the effect of helical cylindrical gear modification parameters on transmission errors is carried out. A surrogate model for helical gear pair transmission errors considering modification parameters is proposed. A methodology for helical gear pair transmission errors optimization that takes multiple modification parameters and their interactions into consideration is proposed and has been verified by vehicle road tests. Abstract: High-frequency noise, which is called gear whine, is a common noise, vibration, and harshness (NVH) problem in the drive axles of commercial vehicles. Although this problem can be solved by gear modification, it is difficult to suppress gear whine effectively because of the difficulty in the selection of the modification parameters. In this paper, on the basis of the combination of the design of experiment (DOE) method and the artificial fish swarm algorithm (AFSA), a method for arriving at the optimal modification design to reduce the peak-to-peak transmission error (PPTE) of helical gear pair is proposed. The method is verified to be effective for reducing gear PPTEs and drive axle vibrations by vehicle road tests with optimized sample pieces. In addition, it is more efficient than the existing methods, as indicated by the results of the gear contact analysis of a coupled dynamic-finite element (FE) model and NVH performance in the tests.